Factors Related To The Occurrence Of Diarrhea In Toddlers In The Working Area Of Telaga Dewa Health Center, Bengkulu City - Febriyanti, Fitria; Sari, Fikitri Marya; Fauzi, Yusran; Darmawansyah, Darmawansyah; Wulandari, Wulandari (Journal Hygeia Public Health, 2024)
Intoduction: Diarrhea is a disease that often causes death in toddlers, with an estimated 443,832 children under the age of 5 dying from diarrhea. The prevalence of diarrhea cases in toddlers in Indonesia increased by 26.4% in 2022. This study aims to identify the risk factors associated with diarrhea in toddlers in the Working Area of Telaga Dewa Health Center in Bengkulu City. Method: This research is quantitative with a cross-sectional design. The sample size for this study was 96 individuals, selected using simple random sampling. Data analysis was performed using the chi-square test with a significance level of 95%. Result and Discussion: he analysis results showed that a portion of the respondents had sufficient knowledge (51.0%), more than half of the respondents had unfavorable attitudes (68.8%), and more than half of the respondents did not provide exclusive breastfeeding (66.7%), while almost one-third of the respondents did not experience diarrhea (32.3%). Based on the bivariate analysis, there was a significant relationship between knowledge and exclusive breastfeeding with the incidence of diarrhea in the Working Area of Telaga Dewa Health Center, Bengkulu City. However, there was one variable that showed no significant relationship between attitude and the incidence of diarrhea at the health center.Conclusion: t is hoped that the health center can optimize preventive and promotional programs regarding factors related to the incidence of diarrhea in toddlers, and that mothers with toddlers understand the factors associated with the occurrence of diarrhea